Concomitant Replacement of the Dilated Ascending Aorta During Aortic Valve Replacement; Does It Increase the Perioperative Morbidity and Mortality Risks?. Issue 3 (16th May 2013) - Lim, Ju Y.; Jung, Sung H.; Kim, Joon B.; Kim, Dong K.; Chung, Cheol H.; Song, Hyun; Lee, Jae W.; Choo, Suk J.
Abstract Background Concerns of increased surgical risks with ascending aortic replacement have led surgeons to manage post‐stenotic aortic dilatation more conservatively during aortic valve replacement (AVR). The present study aimed to assess the prognostic implications and surgical risks of replacing the dilated aorta during AVR. Methods Between January 1999 and March 2010, 134 patients who received surgery for aortic stenosis and post‐stenotic dilatation (aorta size ≥40 mm) were included in the present study. AVR was performed in 92 patients (AVR group) while aortic valve and ascending aorta replacement (AVR + aorta group) were performed in 42 patients. Overall survival was compared between the two groups using Cox proportional hazard model after adjustment with inverse‐probability‐of‐treatment weighting. Results The mean follow‐up duration was 3.5 ± 3 years. There were no significant differences in the operative mortality and morbidity between the two groups. The late cardiac deaths were also not significantly different between the two groups (p = 1.00). In the AVR group, the ascending aortic expansion rate which was 0.18 mm/year over a mean follow‐up duration of 2.3 ± 2.2 years by echocardiography showed a positive correlation with time (r = 0.3, p = 0.08). A relatively greater aortic expansion rate was identified as a risk factor for late mortality (p = 0.015, HR 1.08 (CI: 1.02 to 1.15). Conclusions Concomitant replacement of the dilated ascending aorta during AVR did not increase the immediate postoperative morbidity or mortality risks and tended to exert a long‐term beneficial effect on the risk of late mortality. doi: 10.1111/jocs.12111 (J Card Surg 2013;28:285–290)